Utilizing ion leaching effects for achieving high oxygen-evolving performance on hybrid nanocomposite with self-optimized behaviors - Daqin Guan (Nature Portfolio, 2020)
Water oxidation catalysis may provide the electrons needed for sustainable fuel production, but catalysts often degrade under working conditions. Here, authors introduce soluble species into perovskites to exert positive ion leaching effects for enhancing perovskite stability and activity.